Dyslipidemia Impacts Cardiometabolic Health and CVD Risk in a Relatively Young Otherwise Healthy Population - Jillian M. Lang; Elena S. Shostak; William K. Quinn; Valerie D. Chervinskaya; Elisa Fioraso; Everett Smith; Christopher J. Kotarsky; Justin A. DeBlauw; Jennifer L. Lloyd; Stephen J. Ives (The Journal of Clinical Hypertension)
ABSTRACT Dyslipidemia, abnormal levels of lipids in the bloodstream, is associated with cardiovascular disease risk (CVD). The purpose of this study was to evaluate the effects of dyslipidemia on cardiometabolic health in relatively young, healthy adults. Participants were 54 healthy males and females aged 18–60 years. Participants were assessed for anthropometrics, body composition, blood pressure and vascular stiffness indicators, microvascular health, and glucose and lipid levels. Using a cross‐sectional approach, participants were characterized and grouped as having dyslipidemia or not, and then statistically assessed to determine whether differences in other cardiometabolic health measures existed between the groups. There were significant differences between groups for body weight and composition (total mass, muscle mass, visceral fat, bone mass, and body mass index, all, p < 0.027, Cohen's d > 0.605) with the dyslipidemia group being higher. There were significant differences between groups for peripheral and central blood pressures (all, p < 0.003, Cohen's d > 0.899), as well as for vascular stiffness indicators (pulse pressure, augmentation pressure, augmentation index, augmentation index 75) (all, p < 0.022, Cohen's d > 0.672) with elevations noted in the dyslipidemia group. Ten‐year CVD risk was significantly different between groups, with an average risk of 0.8% in the normal lipids group and a risk of 5.4% in the dyslipidemia group (p < 0.001, Cohen's d = 1.260). However, there were no significant differences in macro‐ or micronutrient intake between groups (all, p > 0.166, Cohen's d < 0.412). There is a significant impact on cardiometabolic health in individuals with dyslipidemia who are otherwise healthy, which may increase individual risk for CVD. Trial Registration: ClinicalTrials.gov identifier: NCT06544915.